Cardiopathy in a domestic dog on the background of obesity (literature review) - Zarytskyi, S.; Lokes-Krupka, T. (Scientific Progress & Innovations, 2022)
The review article provides data from literary sources, both domestic and foreign authors, regarding the causes of obesity in domestic dogs and how obesity affects the development of other various diseases or disorders that have potentially serious consequences for the animal's body. Cardiovascular and respiratory pathologies, fatty dystrophy of internal organs, joint dysplasia, osteoarthritis, urolithiasis, and dermatological lesions are among the diseases that arise as a result of obesity. Of the diseases mentioned above, structural and functional changes of the heart are most often registered in obese animals, namely cardiopathies of various forms: dilated, hypertrophic and restrictive. Unlike hypertrophic and restrictive cardiopathies, which are rarely diagnosed in dogs, much attention is paid to the study of the dilated form of cardiopathy. The true causes of the occurrence of this pathology are not known for certain, researchers in the field of veterinary medicine to this day cannot determine the only cause of the development of the dilated form of cardiopathy. Scientists single out many different etiological factors, common among them are: poor nutrition, metabolic disorders, excess body weight, amino acid deficiency. Dilated cardiopathy is one of the most frequent causes of death among dogs of certain breeds, and that is why researchers continue to investigate methods of identifying sick animals in the asymptomatic stage of the disease. The dilated form of cardiopathy can lead to expansion and thinning of the wall of the left ventricle of the heart, which in turn leads to violations of the contractile function of cardiomyocytes and the occurrence of systolic and diastolic dysfunction of the myocardium. Dysfunctions of the myocardium can lead to the development of heart failure, ascites, vasospasm or cardiogenic shock. Even sick animals that do not have obvious clinical signs of the disease at the initial stage of the pathology develop congestive heart failure or sudden cardiac death. That is why our goal is to search the literature for the results of domestic and foreign scientists regarding cardiopathy against the background of obesity in a pet dog.